2019
DOI: 10.1186/s12917-019-1944-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA miR-26b as a potential diagnostic biomarker of degenerative myelopathy in Pembroke welsh corgis

Abstract: Background Degenerative myelopathy (DM) is a progressive neurodegenerative disease frequently found in Pembroke Welsh Corgis (PWCs). Most DM-affected PWCs are homozygous for the mutant superoxide dismutase 1 ( SOD1 ) allele; however, the genetic examination for the SOD1 mutation does not exclusively detect symptomatic dogs. In order to identify novel biomarkers, the plasma microRNA (miRNA) profiles of PWCs with DM were investigated. Results Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The 10-week moderate-intensity swimming exercise enlarged and thickened cardiomyocytes. Although an increase in cardiomyocyte volume is also observed in pathological cardiomegaly, increased fetal gene expression such as ANP, BNP, b-MHC were also significantly upregulated in pathological LVH (Swynghedauw, 1986;Dorn et al, 1994;Bernardo et al, 2010;Nakamura and Sadoshima, 2018;Oldfield et al, 2019). In our swimming exercise-induced cardiomyocyte hypertrophy, the expression of ANP, a-actin, and the ratio of b-MHC to a-MHC was not significantly changed, indicating a physiological LVH model was successfully induced.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…The 10-week moderate-intensity swimming exercise enlarged and thickened cardiomyocytes. Although an increase in cardiomyocyte volume is also observed in pathological cardiomegaly, increased fetal gene expression such as ANP, BNP, b-MHC were also significantly upregulated in pathological LVH (Swynghedauw, 1986;Dorn et al, 1994;Bernardo et al, 2010;Nakamura and Sadoshima, 2018;Oldfield et al, 2019). In our swimming exercise-induced cardiomyocyte hypertrophy, the expression of ANP, a-actin, and the ratio of b-MHC to a-MHC was not significantly changed, indicating a physiological LVH model was successfully induced.…”
Section: Discussionmentioning
confidence: 58%
“…Given LVH in response to endurance exercise is protective, the miRNA changes in physiological LVH is supposed to be adaptive and to promote moderate autophagy which is essential for physiological LVH. Of note, miR-26b-5p, miR-204-5p, and miR-497-3p had been detected in plasma and were used as a potential diagnostic biomarker for diseases such as lung cancer (Du et al, 2015;Guo et al, 2015;Lu et al, 2018;Nakata et al, 2019). Distinct plasma gradients of miR-204-5p in the pulmonary circulation were observed in patients with different pulmonary hypertension subtypes (Estephan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have showed that miR-26b served as a novel diagnostic biomarker for degenerative myelopathy. 22) Moreover, by regulating DEPDC1 gene, miR-26b acted as a tumor suppressor in triple negative breast cancer. 23) Ovchinnikova et al found that miR-26b was associated with increasing acuity of heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Aside from these routinely used diagnostic techniques, new molecular techniques are being developed. In a recent study on PWCs, a positive correlation between increases in the plasma levels of miR-26b and disease progression has been discovered (Nakata et al, 2019). MiR-26b is a microRNA (miRNA), i.e.…”
Section: Diagnosing Dm Clinicallymentioning
confidence: 99%